Cardiovascular MRI in Congenital Heart Disease An Imaging Atlas - Sridharan, Shankar; Price, Gemma; Tann, Oliver; Hughes, Marina; Muthurangu, Vivek; Taylor, Andrew M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This new and unique clinical resource offers rapid access to high-quality images covering a broad spectrum of paediatric and adult cardiac pathologies visualized using MRI and CT. Key images of each condition and a clear interpretation of their MR appearances allow for greater understanding of the pathology. Focus is given to the planning of imaging planes, techniques and sequences to obtain the best images and improve MR assessment. This text would benefit all health professionals involved in imaging congenital cardiac disease.
Technical Considerations -- MR Imaging Under GA -- Imaging Protocol -- Normal Anatomy-Axial -- Normal Anatomy-Coronal -- Normal Anatomy-Sagittal -- Image Planes-Ventricles -- Imaging Planes-Left Ventricular Outflow Tract -- Imaging Planes-Right Ventricular Outflow Tract -- Imaging Planes-Branch PAs -- Imaging Planes-Tricuspid Valve -- Imaging Planes-Coronary Arteries -- Atrial Septal Defect -- Sinus Venosus Defect -- Atrioventricular Septal Defect -- Ventricular Septal Defect -- Aortic Valve Stenosis -- Aortic Valve Incompetence -- Coarctation of the Aorta -- Repaired Coarctation of the Aorta: Complications -- Interrupted Aortic Arch -- Aortic Vascular Rings -- Left Pulmonary Artery Sling -- Marfan Syndrome -- Williams Syndrome -- Mitral Stenosis -- Mitral Regurgitation -- Hypertrophic Cardiomyopathy -- Dilated Cardiomypathy -- Noncompaction Cardiomyopathy -- Tetralogy of Fallot -- Tetralogy of Fallot: Repaired -- Pulmonary Stenosis -- Percutaneous Pulmonary Valve Implantation -- Pulmonary Atresia and VSD -- Transposition of the Great Arteries: Arterial Switch Operation -- Transposition of the Great Arteries: Senning and Mustard Repair -- TGA with VSD and PS -- Congenitally Corrected Transposition of the Great Arteries -- Common Arterial Trunk -- Double Outlet Right Ventricle -- Double Inlet Left Ventricle -- Hypoplastic Left Heart Syndrome: Norwood Stage 1 -- Bi-directional Cavo-pulmonary (Glenn) shunt -- Fontan-Type Circulation (Tricuspid Atresia) -- Total Cavo-pulmonary Connection -- Anomalous Coronary Arteries -- Anomalous Left Coronary Artery from Pulmonary Artery -- Kawasaki Disease -- Total Anomalous Pulmonary Venous Drainage -- Partial Anomalous Pulmonary Venous Drainage -- Ebstein's Anomaly -- Right Isomerism -- Left Isomerism -- List of Abbreviations -- Further reading.
Keywords: Medicine; Radiology, Medical; Cardiology; Pediatrics; Surgery; Medicine & Public Health; Cardiology; Imaging / Radiology; Pediatric Surgery; Pediatrics